1989
DOI: 10.2337/diab.38.10.1329
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Mediated Islet Cell Cytotoxicity in BB Rats

Abstract: Islet cell killing mediated by natural killer cells and T-lymphocytes in diabetes-prone (DP) and diabetic BB rats has been described, but other killing mechanisms may also be involved. Histopathologic studies suggest that macrophages are the first immune cells to infiltrate islets. To determine if macrophages are the first cells mediating islet damage, macrophagemediated cytotoxicity was evaluated in BB rats of different ages. Splenic macrophages isolated from DP rats at 33,100,120, and 140 days of age showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
1
3
1
Order By: Relevance
“…This to some extent may also explain the lack of MHC restriction on islet cytolytic events. Our functional data are consistent with those non-restricted cytolytic data observed using spleen effector cells in previous studies [24,25]. This killing is unlikely to be alloreactivity since similar results are obtained using Wistar Furth or DP islet target cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This to some extent may also explain the lack of MHC restriction on islet cytolytic events. Our functional data are consistent with those non-restricted cytolytic data observed using spleen effector cells in previous studies [24,25]. This killing is unlikely to be alloreactivity since similar results are obtained using Wistar Furth or DP islet target cells.…”
Section: Discussionsupporting
confidence: 92%
“…This killing is unlikely to be alloreactivity since similar results are obtained using Wistar Furth or DP islet target cells. Our previously reported data of non-restricted splenic derived macrophage-mediated islet cytolysis could be related to total islet effector cell killing reported herein [24]. These data do not indicate which cell subtype(s) is (are) the major islet effector cell.…”
Section: Discussioncontrasting
confidence: 52%
“…Similar to the NOD mouse, macrophage-depleting silica treatment of DP-BB rats almost completely abrogates onset of spontaneous T1D (142). In addition, tracking the immune infiltration throughout disease progression revealed that macrophages are the initial infiltrating immune cells into the islets of DP-BB rats (65,102,209), and that macrophages can also play an effector role during the autoimmune attack (95,99,132). In addition to murine models of autoimmune diabetes, histological analyses of pancreata sections from patients with T1D have also demonstrated an influx in macrophage recruitment into the islets (66,79,82,165).…”
Section: A Critical Innate Immune Cell Type In T1dmentioning
confidence: 87%
“…The autoimmune response triggering type 1 diabetes relies on the crosstalk between pancreatic beta cells and the immune system. Histology insulitis results obtained from experimental models of type 1 diabetes and type 1 diabetes patients demonstrate that macrophages and dendritic cells are the first cells that infiltrate into the islets (Nagy et al 1989;Dahlén et al 1998;Jörns et al 2014;Walker et al 1988;Hanenberg et al 1989). Macrophage polarization is defined into two broad subsets: the classically activated M1 macrophages and alternatively activated M2 macrophages.…”
Section: Introductionmentioning
confidence: 99%